A Racialized View of Entrepreneurship: A Review and Proposal for Future Research - Bruton, Garry D.; Lewis, Alexander; Cerecedo-Lopez, Jose A.; Chapman, Kenneth (Academy of Management Annals, 2023)
Entrepreneurship research, as with most organizational research, almost always adopts a race-neutral lens in which racial inequality is understood as exogenous to organizational theories. This approach is problematic because entrepreneurship is an embedded process and cannot be understood independent of its contexts, and the contexts in which it unfolds are often marked by racial inequality despite absence of overt racial antipathy. We examine over 100 articles that address entrepreneurship and race, with a focus on underrepresented minorities in the United States – African, Hispanic, and Native Americans. From these articles, we not only derive why minority entrepreneurs continue to be disadvantaged despite widespread support for their entrepreneurship, but we also elevate themes of racial agency endemic to entrepreneurship from marginalized racial positions. We argue that entrepreneurship research needs to consider race; that is, scholars need to incorporate racialized structures into their theorizing. Doing so not only will highlight the structural underpinnings of racial disadvantage for URM entrepreneurs, but it also casts entrepreneurship as an essential mechanism for racial agency.